Effectiveness of CAD-CAM Application for the Development design and implementation of maintenance tools - Yusuf Effri Prastyo Budi; Tedjo Sukmono (Postgraduate, University of Mataram, 2023)
This study aims to evaluate the effectiveness of using Computer-Aided Design and Computer-Aided Manufacturing (CAD-CAM) applications in developing the design and implementation of maintenance tools. The use of CAD-CAM has become a major trend in the modern manufacturing industry because it provides various advantages such as time efficiency, high precision and increased productivity. However, it is important to assess the true effectiveness of this technology in the context of maintenance tool development to fully understand its potential benefits. The literature review analysis method was used to compile an in-depth review of the latest research and publications related to the use of CAD-CAM in the design development and implementation of maintenance tools. A number of case studies and field experiments were also included in the analysis to provide further insight into the application of this technology in various industrial environments. The results of the analysis show that the use of CAD-CAM in the development of maintenance tool designs has brought significant positive changes. This application is able to reduce development cycle time, enable model-based engineering, and improve modeling accuracy. Apart from that, CAD-CAM also facilitates better collaboration between design teams, engineers and other stakeholders, which contributes to improving the quality of the final product. However, despite the many benefits offered by CAD-CAM, there are also challenges that need to be overcome to increase the effectiveness of its use. Some of these are high initial investment costs, the need for higher technical skills, and complex integration with existing infrastructure. In conclusion, CAD-CAM has proven effective in developing the design and implementation of maintenance tools. With this technology, companies can increase operational efficiency, improve product quality, and gain a competitive advantage in the market. By understanding the benefits and challenges of its use, professionals can more effectively adopt CAD-CAM and fully exploit its potential in the modern manufacturing industry.